Separated children in foster care in the Republic of Croatia - Brajša-Žganec, Andreja; Keresteš, Gordana; Kuterovac-Jagodić, Gordana, Lebedina-Manzoni, Marija Selak-Živković, Aleksandra (2005)
The Centre for Social Policy Initiatives in co-operation with the Ministry of Health and Social Welfare and the University of Zagreb is implementing a three-year training program for experts, professionals and foster parents in the area of foster care in the Republic of Croatia with the support of Swedish experts and professionals. The expected results of the three-year program are to widen the practice and improve the quality of foster care in the Republic of Croatia, especially in urban areas. Implementation of this program will also train experts in the field of foster care, as well as professionals and foster parents. The aim of this paper is to show the situation of separated children placed in foster care within the context of deinstitutionalisation processes in the Republic of Croatia. Focus group discussions with 20 foster parents and 13 professionals in social welfare, as well as the results of applied research on public opinion about foster care in the Republic of Croatia will be used to describe the situation of separated children in foster care placements. Data indicate how foster parents and professionals perceive the established practice of foster care in the Republic of Croatia and show their views concerning needed and possible improvements of foster care practice. The achieved results of focus group discussions as well as public opinion data on foster care placement practice in Croatia significantly indicate how to improve the quality of foster care. This is particularly related to the need of continuous support to foster parents and consequent monitoring of children placed with foster families.
Projekt MZOS
Projekt MZOS
ENG